Literasi Literasi Sejarah Sebagai Upaya Penanaman Karakter Bagi Anak - Hera Hastuti; Zafri Zafri; Iqrima Basri (Diakronika, 2019)
Education is the main way to advance a nation. Progress is not only in terms of technological or physical aspects but also progress in human behavior and civilization. So it is not strange that the character of the people of a nation is a reflection of the quality of education. At present, the problem of the character of Indonesia's young generation is crucial to be overcome. The decline in character does not only occur in children with minimal education, but also occurs in children with secondary schooling. Many cases are related to this character decline, for example in Nagari Sungai Nyalo, Pesisir Selatan Regency. Nagari Sungai Nyalo as an active area in tourism, but not accompanied by changes in the behavior of its generation for the better, is evident that there are still many children of Nagari Sungai Nyalo who extort extortion to tourists, besides the spoken language has not been used reflecting the values of politeness. Facing this problem several attempts were made, one of which was the inculcation of character values through historical literacy. The essence of history is a storehouse of values and characters, one of which can be obtained through the story of historical figures, such as; Buya Hamka, Mohammad Hatta, Agus Salim, Natsir, Tan Malaka and other historical figures. These figures are great figures who not only have intellectual intelligence but also have extraordinary character and character. The moral values and personalities of these figures need to be instilled in the younger generation of children, as the authors have done with the children of Nagari Sungai Nyalo in Pesisir Selatan Regency.